2018
DOI: 10.15850/ijihs.v6n2.1318
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rate after Intrauterine Insemination with the Presence or Absence of Leukocytospermia in Sperms Prepared using Density Gradient Method

Abstract: Objective: To examine the association between different concentrations of leukocyte and sperm recovery rate after sperms are prepared using density gradient method and pregnancy rate after intrauterine insemination (IUI). Increased leukocytes in semen have been associated with increased reactive oxygen species (ROS) that reduces sperm quality.Methods: Semen samples that were collected from 31 male partners of couples undergoing infertility investigation were analyzed for sperm concentration, motility, and leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…From these data it can also be said that leukospermic patients experience less success than non-leukospermic patients. 18 Infertility can be affected by a history of smoking. 19 It has been shown that smoking has a negative impact on infertility.…”
Section: Discussionmentioning
confidence: 99%
“…From these data it can also be said that leukospermic patients experience less success than non-leukospermic patients. 18 Infertility can be affected by a history of smoking. 19 It has been shown that smoking has a negative impact on infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Pada wanita berusia lebih dari 40 tahun, hanya sedikit kehamilan yang tercapai setelah 3 kali inseminasi siklus. Penelitian (Widyastuti et al, 2018) menunjukkan bahwa bahkan setelah beberapa siklus inseminasi tingkat kehamilan bisa cukup baik. Studi lain, bagaimanapun, telah melaporkan penurunan yang kuat dalam angka kehamilan setelah hanya beberapa siklus.…”
Section: Keberhasilan Berdasarkan Faktor Usiaunclassified
“…The optimum concentration of ROS involved in diverse physiological functions of sperm, including capacitation, acrosome reaction, and binding to the zona pellucida (Chen et al, 2013). However, it has been proven that the ROS has negatively impacted the premature acrosome reaction that correlates to the inability of rat epididymal sperm in penetrating the zona-intact of the oocyte (Widyastuti et al, 2018). the ROS level within group D may be increased, so induced the imbalance between ROS and antioxidant concentration.…”
mentioning
confidence: 99%